Altered Effective Connectivity within the Language Network in Primary Progressive Aphasia - Sonty, Sreepadma P; Mesulam, M.-Marsel; Weintraub, Sandra; Johnson, Nancy A; Parrish, Todd B; Gitelman, Darren R (The Journal of neuroscience, 2007)
Primary progressive aphasia (PPA) is a neurodegenerative dementia syndrome principally characterized by the gradual dissolution of language functions, especially in the early stages of disorder. In a previous functional neuroimaging study, PPA patients were found to activate core language areas similarly to control subjects when performing semantic and phonological processing tasks (Sonty et al., 2003). In the present study, functional magnetic resonance imaging (fMRI) and dynamic causal modeling (DCM) were used to study multiregional effective connectivity in early-stage PPA ( n = 8) and control ( n = 8) subjects performing semantic word matching and visual letter matching tasks. fMRI analysis showed semantic task-specific activations in the left inferior frontal (Broca's area) and posterior superior temporal (Wernicke's area) regions, in addition to other language regions, in both groups. Using a model language network consisting of six left hemisphere regions, the DCM analysis demonstrated reduced language-specific effective connectivity between Wernicke's and Broca's areas in the PPA patient group. Furthermore, this decrement in connectivity was predictive of semantic task accuracy. These results demonstrate for the first time that dysfunctional network interactions (effective connectivity), rather than hypoactivity within individual brain regions, may contribute to the emergence of language deficits seen in PPA.